Application of robot-assisted radical prostatectomy in men over 75 years: an analysis of comparative outcomes. (31st December 2023) - Xia, Zhongyou; Fu, Xueqin; Li, Jinze; Yuan, Xinzhu; Wu, Ji; Tang, Lingtong
Abstract: Objective: This study aimed to summarize the current evidence regarding the feasibility of robot-assisted radical prostatectomy (RARP) in men aged over 75 years. Method: A comprehensive search of four electronic databases (China National Knowledge Infrastructure, PubMed, Web of Science, and Cochrane Library) was performed to identify eligible comparative studies as of April 2022. Parameters, including perioperative results and oncological and functional outcomes, were evaluated. Results: Seven articles with 7575 patients undergoing RARP were included in this study. Patients with prostate cancer were grouped by age ≥ 75 years versus < 75 years. Our results demonstrated that compared with the older group, the younger group had better potency ( p  < .00001). However, there were no significant differences in operation time ( p  = .29), estimated blood loss ( p  = .13), length of hospital stay ( p  = .48), complications ( p  = .22), continence ( p  = .21), positive surgical margin ( p  = .28), and biochemical recurrence ( p  = .74) between the groups. Conclusion: Our study revealed that the perioperative, oncological, and functional outcomes in men aged over 75 years undergoing RARP were not significantly different from those of their younger counterparts. RARP is feasible in men aged over 75 years.